2021
DOI: 10.3389/fncel.2021.633735
|View full text |Cite
|
Sign up to set email alerts
|

The Oral-Gut-Brain AXIS: The Influence of Microbes in Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is one of the most frequently diagnosed neurodegenerative disorders worldwide and poses a major challenge for both affected individuals and their caregivers. AD is a progressive neurological disorder associated with high rates of brain atrophy. Despite its durable influence on human health, understanding AD has been complicated by its enigmatic and multifactorial nature. Neurofibrillary tangles and the deposition of amyloid-beta (Aβ) protein are typical pathological features and fundam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 96 publications
0
51
0
2
Order By: Relevance
“…Although the same severity of caries based on DMFT/dmft was shown in NCPCS and CPCS, the enrichment of P. endodontalis and P. micra indicates deeper caries progression in CP children. The SPM of CP children and their toxic metabolite [e.g., short-chain fatty acid (SCFA)] may invade the pulp through dentinal tubules, causing irreversible pulpitis and even invading the bloodstream via the pulp capillaries ( Figure 7 ) ( Narengaowa et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the same severity of caries based on DMFT/dmft was shown in NCPCS and CPCS, the enrichment of P. endodontalis and P. micra indicates deeper caries progression in CP children. The SPM of CP children and their toxic metabolite [e.g., short-chain fatty acid (SCFA)] may invade the pulp through dentinal tubules, causing irreversible pulpitis and even invading the bloodstream via the pulp capillaries ( Figure 7 ) ( Narengaowa et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This location is more likely to impact PD pathology, consistent with Braak’s hypotheses and PD subject autopsy data 7 . Prior studies have demonstrated that microbial communities are distinct in different parts of the body including different skin sites 20 , multiple locations along the GI tract 21 , and different locations within the oral cavity 22 . Similarly, we hypothesized that the deep nasal sinus cavity microbiome is unique, and that data from the oro-nasal cavity may not sure as a viable proxy for the deep nasal sinus cavity microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that oral microbiome significantly affected the composition of gut microbiome ( Hou et al, 2021 ; Pandya et al, 2021 ; Park et al, 2021 ). The oral microbiome and gut microbiome can spread to the brain through cranial nerves or cellular infections or produced certain metabolites to affect the brain by both direct and indirect means ( Dominy et al, 2019 ; Jing et al, 2021 ; Narengaowa et al, 2021 ; Vyhnalova et al, 2021 ; Wang et al, 2021 ). Our results showed significant differences in oral microflora between HGG patients and HCs; oral Patescibacteria was significantly decreasing during the progression of glioma malignancy.…”
Section: Discussionmentioning
confidence: 99%